SAT0189 Factors influencing the prescription of tocilizumab alone or in combination with dmards in rheumatoid arthritis patients in a real life setting. pooled analysis of 3 observational studies. (15th June 2017) - Saraux, A; Cantagrel, A; Combe, B; Flipo, R-M; Idier, I; Baffie, C; Tebib, J
Abstract : Background: Tocilizumab (TCZ) as monotherapy (Mono) is nowadays a standard treatment in rheumatoid arthritis (RA) for patients in whom methotrexate (MTX) is inappropriate 1 . Objectives: To describe factors influencing the use of TCZ in Mono or in combination with DMARDs (Combo) in real-life practice in RA patients (pts). Methods: Analysis: pooled data of 3 prospective, multicentre, observational studies (PEPS n=610, Spare-1 n=307, Act-solo n=577). Patients: RA pts requiring TCZ treatment according to their physician. Treatment: TCZ as prescribed in real life. Endpoint: Evaluation of factors influencing the use of TCZ in Mono or in Combo. Data collected: demographic characteristics, past medical history, RA characteristics and history including previous RA treatments, TCZ treatment strategy (Mono or Combo). Statistical analysis: Pts fulfilling inclusion and non-inclusion criteria and with ≥1 TCZ infusion were analyzed. 1- descriptive analysis 2- Univariate and multivariate analysis to determine factors influencing the use of TCZ in Mono. Variables with more than 20% of missing data were excluded from the multivariate model. Results: 1494 pts (3 studies) were analysed at inclusion. Pts' characteristics: 56% of the pts were >55 years old, 79.6% female, mean RA duration 11.1±9.3 years, 83.0% positive for rheumatoid factors and/or ACPA, 77.3% with erosive disease on X-rays, mean ESR 29.9±23.1mm, mean CRP 19.9±26.2 mg/l mean DAS 28-ESR 5.21±1.22, mean HAQ-DI 1.56±0.68, and mean pain VAS 61.5±23.2. Past RA treatment included csDMARDs in 98.5% and biologics in 77.8% (median=2 [1–6]). TCZ was initiated as Mono in 36.4% of pts and in Combo in 63.6%, with MTX in 83.3% of Combo pts (mean dose 15.7±4.4mg/week). Corticosteroids were used in 74% of pts (mean dose 10±7mg/day). Variables associated with a TCZ prescription in Mono were age (≥65 years), number of previous bDMARD, use/dose of steroids, ESR/CRP values, VAS global activity (physician and pt), pain VAS and HAQ-DI. In the multivariate analysis, variables associated with a TCZ prescription in Mono were age ≥65 years (OR=1.71 [1.30 - 2.24], p<0.001), number of previous bDMARD (1 bDMARD, OR=1.35 [0.94 - 1.92], 2 bDMARD OR=1.82 [1.28 - 2.60], ≥2 bDMARD, OR=1.19 [0.82 - 1.71] p=0.006), higher pain VAS (OR=1.09 [1.04 - 1.15], p=0.001), higher ESR value (OR=1.07 [1.02 - 1.12], p=0.013). Conclusions: This pooled analysis suggests that physicians preferably prescribe TCZ alone in older patients, heavily treated before, with higher inflammatory markers and higher pain VAS. This use might be explained by physicians' reluctance to prescribe the association in frailer patients and complementary data on comorbidity factors will be analysed to support this hypothesis. References: JS. Smolen et al, Ann Rheum Dis doi:10.1136/annrheumdis-2013–204573. Disclosure of Interest: A. Saraux: None declared, A. Cantagrel: None declared, B. Combe Consultant for: Chugai Pharma France, R.-M. Flipo Consultant for: Chugai Pharma France, I. Idier Employee of: Chugai Pharma France, C. Baffie Employee of: Altizem for Roche SAS, J. Tebib: None declared